2000
DOI: 10.1038/sj.cgt.7700223
|View full text |Cite
|
Sign up to set email alerts
|

Immunological responsiveness to interleukin-2-producing brain tumors can be restored by concurrent subcutaneous transplantation of the same tumors

Abstract: The central nervous system shows tolerance for activated host immune reactions, and this relative unresponsiveness may lessen the efficacy of an immunotherapy for brain tumors. Using interleukin-2 (IL-2)-producing 9L rat gliosarcoma cells (9L/IL-2), we examined whether secretion of IL-2 from subcutaneous (s.c.) and/or intracerebral (i.c.) tumors can elicit augmented immunological responses to brain tumors. Syngeneic rats could reject 9L/IL-2 cells inoculated s.c., but developed 9L/IL-2 brain tumors by i.c. ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…We have found that from the wide panel of cytokines, only IL -2 -, 8 IL -4 -, IL -12 -, 8 and GM -CSF -secreting vaccines prolonged lifetime and cured substantial proportion of glioma -bearing mice. This is in good agreement with previous findings that GM -CSF, 15 -17,28,30 IL-4, 15,18,19,22,25 IL -12, 21,24 or IL -2 21,23,3133 production by cancer cells is in association with prolonged antitumor effect.…”
Section: Discussionsupporting
confidence: 93%
“…We have found that from the wide panel of cytokines, only IL -2 -, 8 IL -4 -, IL -12 -, 8 and GM -CSF -secreting vaccines prolonged lifetime and cured substantial proportion of glioma -bearing mice. This is in good agreement with previous findings that GM -CSF, 15 -17,28,30 IL-4, 15,18,19,22,25 IL -12, 21,24 or IL -2 21,23,3133 production by cancer cells is in association with prolonged antitumor effect.…”
Section: Discussionsupporting
confidence: 93%
“…This experimental brain tumor model using 9L cells has a quite stable property; the animals are 100% fatal between 18 and 25 days after inoculation and all the untreated tumors are visible by MRI on day 7 with a mean size of 8.0 F 6.0 mm 3 (16,17). When treated with hIL2-SeV/DMDF and the vaccination, the observed tumor volumes on day 21 were not different between the eliminated tumors and the other progressing tumors.…”
Section: Discussionmentioning
confidence: 83%
“…transplantation of interleukin 2 (IL-2) -producing cells in the rat brain tumor model (16,17). For clinical application of the cytokine gene therapy strategy, however, the cell-mediated therapy needs a large amount of cytokine-producing cells to cover the whole tumor areas in the human brain.…”
mentioning
confidence: 99%
“…When syngeneic 9L tumor cells engineered to express IL-2 were introduced into the CNS of rats, it was found that tumors developed in the CNS. These grew more slowly than wild-type tumors, but all of the animals eventually succumbed to the disease irrespective of IL-2 expression [130]. It was later found by the same group that IL-2 producing cells transplanted into the CNS could effectively eliminate established tumors by inducing immunity in peripheral tissues.…”
Section: Il-2mentioning
confidence: 99%